Polityka państwa wobec Katolickiego Uniwersytetu Lubelskiego w latach 1944–1968 - Gałaszewska-Chilczuk, Dorota (Pamięć i Sprawiedliwość, 2006)
The Catholic University of Lublin was the fi rst university reactivated in Poland after the second world war. The event took place on 21st August 1944 only a month after liberation of Lublin and the fi rst classes at the University were conducted on 3rd November the same year. It may seem paradoxical that the fi rst open university in the communist, totalitarian country was the private, Catholic University of Lublin. However, this university was necessary for the government as a political tool against the Catholic Church.There were two controversial tendencies concerning the policy towards Catholic University in Lublin for the whole period concerning this article. One of them assumed appointing priests on the positions at the University, which is equal to depriving the lay people the chance of being educated there. It would mean making the University less important and would not let realize the credo Deo et Patriae.The second conception which was implemented assumed that the University would be fully controlled by the government. The decree of 1947 and two regulations (from 1951 and 1958) concerning higher education made such a control possible. According to them the government was entitled to validate the statute and University authorities and have influence on didactic process and recruitment. of students.We must admit that the government was successful in administrative control over Catholic University of Lublin. The unwanted professors were dismissed from the University and the new departments were opened and closed according to the current policy. The limit of admission to the University was introduced.The government also used the capabilities of law enforcement agencies. None of the historians has established so far to what extent the University was under surveillance. The new reports are continually being published by the Institute of National Remembrance. The impact of security service to control Catholic University of Lublin was obvious. We should not also forget that the government used other equally efficient tools.